Analysis of Development Inequality in Bengkulu Province for the Period Before the Expansion was Completed, after the Expansion and Currently - Hikari Edelweis Silalahi; Azansyah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine the classification of economic growth and analyze development inequality in Bengkulu Province before the expansion was completed, after the expansion and the current period. This analysis method uses descriptive analysis with the Klassen Typology and Williamson Index (WI), and uses publication data from BPS Bengkulu Province (2005-2007), (2012-2015) and (2020-2022). The results of the Klassen Typology show that every period there is always a change in regional structure in each district in Bengkulu Province, but it does not apply to the city of Bengkulu. The level of development inequality shows the average williamson index before the expansion was completed, after the expansion and is currently at 0.34, 0.37 and 0.427.